The Critical Path Method In Management Information System of Contractor Service Company Using Incremnetal Model (Buana Information Technology and Computer Sciences (BIT and CS), 2023)
Good control is needed in managing a project, starting from controlling the human resources to systematic scheduling. CV. XYZ Surabaya is a contractor service company, that does not yet have an information system that can be used as a control tool in project management. Critical Path Method (CPM) is one method that can be used to schedule projects. This study aims to design a project management information system by implementing CPM. The system design is done using the Incremental Model. The results of this study are in the form of a prototype system that fits the needs of CV. XYZ Surabaya, includes system flow, Contextual Data Model (CDM), and User Interface (UI).